Divine exultation and agony in the face of evil, a creation theodicy of divine restraint - R. Potgieter (Acta Theologica)
Horrendous evil describes the anthropological view of excessive evils which devastate and dehumanise both victim and perpetrator, casting doubt as to whether life is worth living. Divine exultation and divine agony are viewed from the perspective of divinity, whose initial creation brought God pleasure and its fall an offence so deep that, though he considered its total destruction, God instead opted for divine restraint.